2020
DOI: 10.7717/peerj.9623
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic next-generation sequencing for the clinical diagnosis and prognosis of acute respiratory distress syndrome caused by severe pneumonia: a retrospective study

Abstract: Background Metagenome next-generation sequencing (mNGS) is a valuable diagnostic tool that can be used for the identification of early pathogens of acute respiratory distress syndrome (ARDS) in severe pneumonia. Little is known about the use of this technology in clinical application and the evaluation of the prognostic value of ARDS. Methods We performed a retrospective cohort study of patients with ARDS caused by severe pneumonia. Samples were collected from patients in the intensive care unit (ICU) of Jia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 28 publications
3
40
0
Order By: Relevance
“…The excessive antibiotic use can lead to resistance and medical resources waste (Webb et al, 2015;Metlay et al, 2019;Ramirez et al, 2020). Zhang et al (2020) found in of immunosuppressed patients with acute respiratory distress syndrome (ARDS) caused by severe pneumonia, the detection of mNGS can significantly shorten the ICU stay, the ventilation time and reduce the ICU cost. The distinct advantage of NGS may can help clinicians more comprehensive evaluation of empiric antimicrobial therapy and make effective adjustments for immunocompromised SCAP patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excessive antibiotic use can lead to resistance and medical resources waste (Webb et al, 2015;Metlay et al, 2019;Ramirez et al, 2020). Zhang et al (2020) found in of immunosuppressed patients with acute respiratory distress syndrome (ARDS) caused by severe pneumonia, the detection of mNGS can significantly shorten the ICU stay, the ventilation time and reduce the ICU cost. The distinct advantage of NGS may can help clinicians more comprehensive evaluation of empiric antimicrobial therapy and make effective adjustments for immunocompromised SCAP patients.…”
Section: Discussionmentioning
confidence: 99%
“…The BALF specimens were divided into aliquots and subjected to conventional microbiological test as well as mNGS test in a pairwise manner. Some specimens were sent to the Vision Medical Co., Ltd. (China) for the mNGS analysis, performing nucleic acid extraction, library construction, high-throughput sequencing, bioinformatics analysis, and pathogen data interpretation according to previous studies ( Li et al., 2020 ; Zhang et al., 2020 ). The other specimens were sent to our microbiological laboratory using conventional methods for microbiological analysis, including bacterial/fungal smear and culture, Pneumocystis jirovecii (PC) smear (Grocott methenamine staining), acid-fast stain and real-time PCR including cytomegalovirus (CMV), influenza virus, respiratory syncytial virus, Legionella, Mycoplasma and Chlamydia spp .…”
Section: Methodsmentioning
confidence: 99%
“…Their results and ours both indicate that the combination of mNGS and conventional test contributes to the diagnostic ratio of the mixed pulmonary infection. Prior studies have shown that mNGS was significantly better at the identification of coinfections than conventional tests like serological antibody, PCR, or culture [ 16 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…But most of the time simply relying on traditional diagnostic methods may lead to a misdiagnosis and delay of the treatment. NGS does not target a specific pathogen, but high-throughput sequencing of nucleic acid is directly performed in samples [24]. NGS is a kind of culture-independent methods, based on removal of human genes, followed by amplification and sequencing of microbial communities, typically through 16S rRNA genes for bacteria, or whole genome.…”
Section: Discussionmentioning
confidence: 99%